Improving Early Childhood Cognition Through the Traditional Congklak Game at PAUD Miftahussalam Probolinggo - Silvi Andriani; Firmansyah; Masyhuri (Beginner: Journal of Teaching and Education Management, 2023)
This research aims to determine the process and results of learning as an effort to improve children's cognitive development through the traditional congklak playing medium for students at PAUD Miftahussalam Probolinggo. This type of research is Classroom Action Research (PTK). In this research, data was obtained through observation using an observation sheet. Data analysis uses descriptive quantitative data analysis. The research results showed that children's cognitive development before the action was still in the beginning to develop category, namely 66%, the research results for cycle I reached 68%, in the developing category and cycle II reached 81% in the very developing category; The use of traditional congklak play media has had a very good impact as shown by the cognitive development of children who have experienced very good development compared to before the action.